Analisis Kesesuaian Ekowisata Pantai Dan Bahari Di Pesisir Perairan Tanjung Kelapa Desa Poopoh Taman Nasional Bunaken - Muhammad Hasan Sahri; Paulus A. Pangemanan; Fabiola B. Saroinsong (Sam Ratulangi University, 2022)
This research aims to analyze the suitability of coastal and marine ecotourism in the waters of Tanjung (Tj) Kelapa, Poopoh Village, Bunaken National Park (TN). The research was conducted from January to March 2022 in the coastal waters of Poopoh Village, Tombariri District, Minahasa Regency, North Sulawesi Province. This research uses the tourism suitability matrix analysis method. The data is taken from literature studies and direct field data measurements, displayed in the form of tables, graphs and images and processed by mathematical calculations for tourism suitability assessment. The research was conducted at 8 research stations, 2 research stations for beach recreation category, 2 research stations for snorkeling tourism category and 4 research stations for diving tourism category. The results showed that the suitability of tourism at the beach recreation research station was in the suitable category and very suitable, the snorkeling tour station was in the suitable category and at the diving tourism station 2 stations were in the suitable category and 2 stations were in the unsuitable category.